Can CAPRIN-1 Be Responsible for the Recurrence Potential of Odontogenic Keratocysts? - Nelli Yildirimyan; Mehmet Ali Altay; İrem Hicran Özbudak (Stilus Optimus, 2024)
Objectives: The purpose of this retrospective study is to compare dentigerous cysts and odontogenic keratocysts for cytoplasmic activation/proliferation - associated protein-1 antibodies via immunohistochemical staining to obtain a new perspective about the specific behavioural characteristics of odontogenic keratocysts at the molecular level. Material and Methods: Forty dentigerous cysts (DC) and forty odontogenic keratocysts (OKC) tissue samples were examined using immunohistochemical staining to detect cytoplasmic activation/proliferation - associated protein-1 (CAPRIN-1) antibodies. Nuclear and/or cytoplasmic staining was evaluated as "positive". Cell staining rate (%) and cell staining intensity were determined, and a staining intensity distribution (SID) score was calculated for each sample. Cases were considered "negative" if they showed no staining for CAPRIN-1 antibodies, thus were given a SID score of zero. According to the SID scores, the expression levels were rated as negative, mild, moderate, or high. Results: Of 80 samples, 16 that could adversely affect immunohistochemical evaluation were excluded. Ten negative, 21 positive and three negative, 30 positive CAPRIN-1 expressions were observed in DC and OKC groups, respectively. The difference between the negative and positive cases within groups was significant only in the OKC group (P = 0.000). The SID score range and mean were 0 to 160 and 31.1 (SD 35.7) for DC and 0 to 160 and 57.3 (SD 42.3) for OKC groups. CAPRIN-1 expression was significantly higher in the OKC group (P = 0.043). Conclusions: The molecular basis for increased mitotic activity, high recurrence rates or presence of satellite cysts in odontogenic keratocysts may be attributed to the expression of cytoplasmic activation/proliferation - associated protein-1.